The College Management Performance is Reviewed from the Perspective of Customers and Financial Perspective (A Case Study On University WR Supratman Surabaya) - Astuti, Hartati Kanty; Widari, Nyoman Sri; Pelitawati, Diah; Gamal, Ahmad (Archives of Business Research, 2017)
One important factor that is used to assess the success of private college is performance. Private colleges continue their efforts to prepare and fine-tune their business strategies in order to survive in the world of education and even become a winner in the competition. Measurement of performance becomes a very important thing. Balanced Scorecard has goals and measurement that is not only a combination of financial and non-financial measurement, but is the result of a top-down process based on the mission and strategy of a private college. The purpose of this study is to determine the effect of Balanced Scorecard model toward performance of future private colleges. The independent variable in this study is the Balanced Scorecard that consists of customer perspective (X1) and financial perspective (X2) while the dependent variable is the performance of the private college (Y). The sample in this study is 100 people covering over half of the students who are active students at the University of W.R. Supratman Surabaya. Method of data processing is using multiple linear regression with SPSS. The result of discussion can be concluded that (1) The customer perspective has a positive effect on the College Management performance, because value t calculated for customer perspective is 2.345 greater than t table (0.659), (2) Financial perspective has a significant effect on the College Management performance, because value t calculated for financial perspective is 3.561 greater than t table (0.659), and (3) The Financial Perspective is the dominant influence on the variable College Management performance because it has a coefficient of determination of partial of 0.116.